EMOTIONAL QUOTIENT (EQ), INTELLECTUAL QUOTIENT (IQ) DAN BUSINESS PERFORMANCE - Rinamurti, Micheline; Ony, Johan Gunady (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this research is to analyze the effect of emotional quotient (EQ) and intellectual quotient (IQ) the owner of pempek business in Palembang to their business performance, so they can reach the goals. Data collected by questioner and depth interview to owner of pempek business in Palembang. Sample in this research are taken by purposive sampling method. The result of this research shown that EQ and IQ, simultanly and partially, give an influence to the business performance of pempek business in Palembang